2023
DOI: 10.1002/aic.18027
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic thermodynamic/kinetic separation of C3H8/CH3F on carbon adsorbents for ultrapure fluoromethane electronic gas

Abstract: Atomic layer etching (ALE) using the environmentally friendly electronic gas fluoromethane (CH3F) is guided for fabricating nanoscale electronic components. The adsorptive purification of CH3F provide a viable direction to remove trace amounts of impurities to produce highly pure CH3F (>99.9999%) for the ALE process. Herein, to remove trace propane (~100 ppm) in CH3F, we report synergetic thermodynamic and kinetic separation of C3H8/CH3F over glucose‐derived carbon molecular sieve CMS‐T, (T as pyrolysis temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Noticeably, bulk Zr‐BTB displayed almost no micropores and very few mesopores (Figure 2B), however, the formation of densely packed layers may cause transformation of pores to a smaller size 31 . With a smaller molecular size of 3.3 Å than that of N 2 , CO 2 was further applied as the probing gas to analyze the adsorption behaviors 32 . From CO 2 isotherms at 195 K, the microporous volumes were calculated as 0.12, 0.23, and 0.24 cm 3 g −1 for bulk Zr‐BTB, 2D Zr‐BTB, and Zr‐BTB/PA‐Co, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, bulk Zr‐BTB displayed almost no micropores and very few mesopores (Figure 2B), however, the formation of densely packed layers may cause transformation of pores to a smaller size 31 . With a smaller molecular size of 3.3 Å than that of N 2 , CO 2 was further applied as the probing gas to analyze the adsorption behaviors 32 . From CO 2 isotherms at 195 K, the microporous volumes were calculated as 0.12, 0.23, and 0.24 cm 3 g −1 for bulk Zr‐BTB, 2D Zr‐BTB, and Zr‐BTB/PA‐Co, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…31 With a smaller molecular size of 3.3 Å than that of N 2 , CO 2 was further applied as the probing gas to analyze the adsorption behaviors. 32 From CO 2 isotherms at 195 K, the microporous volumes were calculated as 0.12, 0.23, and 0.24 cm 3 g À1 for bulk Zr-BTB, 2D Zr-BTB, and Zr-BTB/PA-Co, respectively (Table 1). The comparation with the results from N 2 tests demonstrated that some inherent micropores cannot be detected by N 2 probe.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…7 Adsorptive separation is considered as a potential alternative technology with broad prospects owing to its energy-and cost-effective features. 8,9 Adsorptive separations based on porous adsorbents can mainly be divided into three categories, including equilibrium separation, 10,11 kinetic separation, 12,13 and molecular sieving. 14−16 It is well known that the molecular sieving mechanism can realize superior separation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The significant advance in porous materials [5][6][7][8][9][10][11][12][13][14][15][16][17] in the last decade has aroused interests of researchers to seek adsorptive separations to make the challenging separation processes more energy-efficient. The developed ordered-assembly porous materials, like metal-organic frameworks (MOFs), [18][19][20][21][22][23][24] covalent organic frameworks (COFs), 25,26 etc, provide an excellent platform for tailor-made porous materials that are adaptive for different guest molecules and have obtained considerable achievements in C 2 H 4 purification.…”
Section: Introductionmentioning
confidence: 99%